Goat’s Milk Production / Muhammad Fakhruddin Johari - Muhammad Fakhruddin, Johari (2020)
Farm Land a company that produces fresh goat milk in powder and bottled for ready drinks to all goat milk enthusiast in Malaysia. Both of these product types that have been commercialized by our company are sourced from local goat milk suppliers which is not imported form another country. This company also providing a variety of flavour for their goat milk according to the taste of the current consumer to make them a satisfactions when purchase the products. Our main purpose is to make a different on our products with the existence product which is using a local goat’s milk. Choosing these local suppliers indirectly can controls the quality of the milk and can improves the country’s economy itself. Farm Land also offered their product at lower price to encourage consumer have a healthy drink. Direct delivery to marketers is also provided by us without charges any additional cost. Farm Land has chose Kulim as their operating locations because it’s close to Penang. This location also a industrial zone and many residential areas around the area. Business has seen an explosion of growth over the year in Kulim and many people stay here because of many job opportunities around and it will cause demand of groceries and beverages arise. Moreover, this area is not yet running business product like ours. So competitors can be reduced. Our marketing strategy is to emphasized the quality and price of our products and services. We offer the affordable price because to attract consumers to choose our product. As we know, this goat’s milk drink is a bit expensive, so we offer buyers the opportunity to enjoy our beverage products at a reasonable price with a high quality. The management of Farm Land have consist of 5 extensive experience workers in in finance, businesses, sale, accounting and food production. They are Fakhruddin as their general manager, Aafiyah as finance manager, Zaim Lukman as administrative manager, Fahmi as marketing manager and Nurul Izzah as operation manager. This company is sole proprietorship by Fakhruddin and these team management will take their role and responsibilities together instead different duties to make the product successful.